Applications of (Big) Data Analysis in A/E/C - Ming-Hung Hsu; Ying-Wu Yang; Zheng-Yun Zhuang (Buildings, 2023)
This editorial paper provides an overview of the Buildings Special Issue (SI), dedicated to the topic “Applications of (Big) Data Analysis in A/E/C” (where A/E/C stands for architecture, engineering, and construction) and the academic papers it includes [...]